The Effects of Using the Sun Safe App on Sun Health Knowledge and Behaviors of Young Teenagers: Results of Pilot Intervention Studies - Isabelle M Clare; Nisali Gamage; Gail A Alvares; Lucinda J Black; Jacinta Francis; Mohinder Jaimangal; Robyn M Lucas; Mark Strickland; James White; Rebecca Nguyen; Shelley Gorman (JMIR Publications, 2022)
BackgroundA balanced approach toward sun exposure and protection is needed by young people. Excessive sun exposure increases their risk for skin cancers such as melanoma, whereas some exposure is necessary for vitamin D and healthy bones. We have developed a new iOS smartphone app-Sun Safe-through a co-design process, which aims to support healthy and balanced decision-making by young teenagers (aged 12-13 years). ObjectiveThe aim of this study was to test the capacity of Sun Safe to improve sun health knowledge and behaviors of young teenagers in 3 pilot intervention studies completed in 2020. MethodsYoung teenagers (aged 12-13 years; N=57) were recruited through the web or through a local school via an open-access website and given access to Sun Safe (29/57, 51%) or a placebo (SunDial) app (28/57, 49%). Participants completed sun health questionnaires and knowledge quizzes before and after the 6-week intervention (either on the web or in class) and rated the quality of the app they used via a survey. ResultsOf the 57 participants, 51 (89%) participants (26, 51% for placebo arm and 25, 49% for the Sun Safe arm) completed these studies, with most (>50%) reporting that they used a smartphone to access their designated app either "once a fortnight" or "once/twice in total." Improved sun health knowledge-particularly about the UV Index-was observed in participants who were given access to Sun Safe compared with those who used the placebo (−6.2 [percentage correct] difference in predicted means, 95% CI -12.4 to -0.03; P=.049; 2-way ANOVA). Unexpectedly, there were significantly more sunburn events in the Sun Safe group (relative risk 1.7, 95% CI 1.1-1.8; P=.02; Fisher exact test), although no differences in time spent outdoors or sun-protective behaviors were reported. COVID-19 pandemic-related community-wide shutdowns during April 2020 (when schools were closed) reduced the time spent outdoors by >100 minutes per day (-105 minutes per day difference in predicted means, 95% CI -150 to -59 minutes per day; P=.002; paired 2-tailed Student t test). Sun Safe was well-rated by participants, particularly for information (mean 4.2, SD 0.6 out of 5). ConclusionsAccess to the Sun Safe app increased sun health knowledge among young teenagers in these pilot intervention studies. Further investigations with larger sample sizes are required to confirm these observations and further test the effects of Sun Safe on sun-protective behaviors.